Segregation for seed weight, pod length and days to flowering following a cowpea cross - Ubi, E.; Mignouna, H.; Obigbesan, G. (African Journals Online, 2001)
Field studies were conducted to evaluate the segregation of the F3 (early generation) and F6 (late generation) families for seed weight, pod length and days to flowering among cowpea inter-sub-specific crosses. A wide range of segregants were provided in this cross and families were highly significantly different in the three agronomic traits studied. The continuous distributions observed for these traits studied in both generations confirms the quantitative nature of inheritance for these traits. Broad sense heritability estimates ranged from 47.8 to 91.1%. Estimates of genetic advance ranged from high to low and were consistent in both generations for all the traits. The F3 and F6 generations were not significantly different in all the three agronomic traits. Intergeneration correlations ranging from 0.35 to 0.49 also revealed strong associations between traits measured in the two generations. A no significant drop was observed between F3 mean and the corresponding F6 mean. This suggests the existence of a good measure of additive and possibly of additive x additive components of variance (which alone are fixable through subsequent inbreeding) although some amount of dominance and duplicate epistasis (which are non-fixable) may also be operative. The results of this study indicate that selection in early generations for superior types is feasible.